2019
DOI: 10.1186/s13104-019-4721-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium houttuyfonate on transcriptome of Pseudomonas aeruginosa

Abstract: ObjectivesThe purpose of this experiment is to analyze the changes of transcriptome in Pseudomonas aeruginosa under the action of sodium houttuyfonate (SH) to reveal the possible mechanism of SH inhibiting P. aeruginosa. We analyzed these data in order to compare the transcriptomic differences of P. aeruginosa in SH treatment and blank control groups.Data descriptionIn this project, RNA-seq of BGISEQ-500 platform was used to sequence the transcriptome of P. aeruginosa, and sequencing data of 8 samples of P. ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The larvae were observed continuously for 84 h and the number of deaths was recorded to determine the survival rate of each group. In view of studies that show that the LD 50 of SNH is 119.14 mg/kg ( Jiang et al, 2006 ) and the LD 100 of SNH is 200 mg/kg ( Lou et al, 2012 ), our research group selected the dose range 1024–32 μg/mL for SH in previous experiments ( Wang et al, 2019 ; Zhao et al, 2019 ). Therefore, the safety range of SNH is large, and it has no obvious cytotoxicity.…”
Section: Methodsmentioning
confidence: 99%
“…The larvae were observed continuously for 84 h and the number of deaths was recorded to determine the survival rate of each group. In view of studies that show that the LD 50 of SNH is 119.14 mg/kg ( Jiang et al, 2006 ) and the LD 100 of SNH is 200 mg/kg ( Lou et al, 2012 ), our research group selected the dose range 1024–32 μg/mL for SH in previous experiments ( Wang et al, 2019 ; Zhao et al, 2019 ). Therefore, the safety range of SNH is large, and it has no obvious cytotoxicity.…”
Section: Methodsmentioning
confidence: 99%
“…Floating motion plays an important role in the pathogenic ability of P. aerugino, which can initiate the adhesion of bacteria to the adhesive surface and contribute to the formation of P. aerugino biofilm. Therefore, these partial results suggest that the inhibition of this motion may be one of the reasons for the reduction of biofilm formation (Diao et al, 2018;Zhao et al, 2019). Furthermore, a recent comparative study by Xu et al (2022) revealed that FA had a greater biofilm repression effect than p-coumaric acid (p-CA) against pathogenic Salmonella enteritidis by binding to proteins involved in flagella motility.…”
Section: Effects On Pseudomonas Aeruginosa Biofilm Formationmentioning
confidence: 97%